Romani Communities and Transformative Change A New Social Europe. - Ryder, Andrew (Policy Press, 2020)
Drawing on Roma community voices and expert research, this book challenges conventional discourses on Romani identity, poverty and exclusion. Through the transformative vehicle of a 'Social Europe', it presents new strategies for framing social justice for Romani communities across Europe and provides innovative solutions to these dilemmas.